2006
DOI: 10.1364/ao.45.002186
|View full text |Cite
|
Sign up to set email alerts
|

Particle-size and velocity measurements in flowing conditions using dynamic light scattering

Abstract: The noninvasive optical technique of dynamic light scattering (DLS) is routinely used to characterize dilute and transparent submicrometer particle dispersions in laboratory environments. A variety of industrial and biological applications would, however, greatly benefit from on-line monitoring of dispersions under flowing conditions. We present a model experiment to study flowing dispersions of polystyrene latex particles of varying sizes under varying flow conditions by using a newly developed fiber-optic DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 3 publications
2
52
0
1
Order By: Relevance
“…In contrast to the typical DLS measurement setup, the time correlation in the on‐line measurement loop was not only influenced by diffusion but also by convective flow (Berne & Pecora, ). It has been previously demonstrated that the convective flow results in increased estimated diffusion coefficients and thus in reduced particle diameters (Leung, Suh, & Ansari, ). The effect was shown to be more pronounced for larger particles.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the typical DLS measurement setup, the time correlation in the on‐line measurement loop was not only influenced by diffusion but also by convective flow (Berne & Pecora, ). It has been previously demonstrated that the convective flow results in increased estimated diffusion coefficients and thus in reduced particle diameters (Leung, Suh, & Ansari, ). The effect was shown to be more pronounced for larger particles.…”
Section: Discussionmentioning
confidence: 99%
“…DLS measurements were successfully applied to analyse sample solutions in flow at different stages of protein folding by Gast et al (1997). A particular fibre optic DLS probe was used by Leung et al (2006) to characterize latex particles in flow, pointing at a variety of potential industrial applications to count and determine the size of particles for quality control in flow. The application of DLS in a shear flow and in a microfluidic channel was mathematically described by Destremaut et al (2009), taking the channel dimensions, shear rates, velocity profile of a Poiseuille flow and interferences of different Doppler shifts into account.…”
Section: Introductionmentioning
confidence: 99%
“…The setup comprises a semiconductor laser (λ=639.4 nm, power=80 μW), a photodetector (avalanche photodiode based photon counting module), a DLS probe built at NASA for both static and dynamic light scattering configurations (scattering angle=163.0 degrees, focal length=16 mm, scattering volume ~50 μm 3 ), a translation stage with a motorized actuator, for accurate positioning, (to which the DLS fiber optic probe is mounted on a multi axis translation stage), and a Pentium based computer containing a digital correlator card (BI-9000) for data acquisition. This system has been previously used in protein crystal growth experiments,30 particle sizing applications in flowing dispersions,31 in protein characterization of ocular tissues in live animals,32 and in clinical ophthalmic applications for the early detection of cataract 33. Only the static (total intensity) light scattering measurements were made in the experiments reported here.…”
Section: Experimental Methodsmentioning
confidence: 99%